2008
DOI: 10.1073/pnas.0707221105
|View full text |Cite
|
Sign up to set email alerts
|

Ecological rules governing helminth–microparasite coinfection

Abstract: Coinfection of a host by multiple parasite species has important epidemiological and clinical implications. However, the direction and magnitude of effects vary considerably among systems, and, until now, there has been no general framework within which to explain this variation. Community ecology has great potential for application to such problems in biomedicine. Here, metaanalysis of data from 54 experiments on laboratory mice reveals that basic ecological rules govern the outcome of coinfection across a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
402
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(413 citation statements)
references
References 50 publications
(69 reference statements)
8
402
1
2
Order By: Relevance
“…By initiating a Th2-driven response in the host, helminths may make the host more susceptible to concurrent infections that are better controlled by Th1 responses and vice-versa (Graham et al 2007 ;Graham, 2008). In the latter context it is, of course, equally possible that, by initiating a Th2 response in the host, one species may make the host environment more conducive to Th2 bias against a second species, also best Mice were given 300 larvae of T. spiralis on day 0, the concurrently infected group having been infected with 300 larvae of H. bakeri 8 days earlier, and were killed in groups on the days shown.…”
Section: The Immune Response As An E N V I R O N M E N T a L S T R E mentioning
confidence: 99%
“…By initiating a Th2-driven response in the host, helminths may make the host more susceptible to concurrent infections that are better controlled by Th1 responses and vice-versa (Graham et al 2007 ;Graham, 2008). In the latter context it is, of course, equally possible that, by initiating a Th2 response in the host, one species may make the host environment more conducive to Th2 bias against a second species, also best Mice were given 300 larvae of T. spiralis on day 0, the concurrently infected group having been infected with 300 larvae of H. bakeri 8 days earlier, and were killed in groups on the days shown.…”
Section: The Immune Response As An E N V I R O N M E N T a L S T R E mentioning
confidence: 99%
“…Most of the time, exclusion occurs through the activation of the host immune system (e.g. Cox 2001; Barton et al 2007;Cattadori et al 2007;Graham 2008), or at least the immune system mediates parasite competition (Bradley & Jackson 2008;Bush & Malenke 2008). Direct interactions may also exist, as in the case of bacteria that live on amphibian skin, excluding infections by pathogenic fungi through the production of fungicides (Harris et al 2009).…”
Section: Definitionsmentioning
confidence: 99%
“…There is increasing evidence that interactions between parasites may also play a significant role in affecting susceptibility of hosts to infection (Hochberg and Holt, 1990 ;Sousa, 1994 ;Petney and Andrew, 1998 ;Cox, 2001 ;Lello et al 2004 ;Maizels et al 2004 ;Faulkner et al 2005 ;Hartgers and Yazdanbakhsh, 2006 ;Cattadori et al 2007Cattadori et al , 2008 ; Lello and Hussell, 2008). However, while these findings indicate that we should consider the whole community of parasites to understand the dynamics of each component species, results from previous studies are not always consistent (Behnke et al 2001 ;Poulin, 2001 ;Behnke, 2008 ;Graham, 2008 ;Telfer et al 2008). Studies in controlled laboratory conditions have not only identified strong parasite interactions but also teased apart some of the molecular mechanisms involved (Curry et al 1995 ;Maizels et al 2004 ;Edwards et al 2005 ;Kamal and El Sayed Khalifa, 2006 ;Graham et al 2007 ;Bradley and Jackson, 2008 ;Fenton et al 2008).…”
mentioning
confidence: 98%